Application of Augmented Reality Technology as an Alternative Media for Campus IT Telkom Purwokerto - Jinan Ghinia Khansa; Cepi Ramdani; Novian Adi Prasetyo (STMIK Budi Darma, 2021)
Augmented Reality is a technology that involves graphics on a computer in the real world, which in the virtual world of three dimensions is brought to the real-world environment in real-time. The application of Augmented Reality technology is currently growing rapidly, including in the field of promotional media. IT Telkom Purwokerto is a private university in Central Java engaged in Information and Communication Technology (ICT). In introducing the campus environment, IT Telkom Purwokerto still uses the manual given to students when PKKMB is also rarely read, and the introduction of buildings uses 3D miniatures by utilising styrofoam where these miniatures are displayed. Based on a survey conducted by researchers to find out the level of difficulty in finding a room at IT Telkom Purwokerto, 70% of respondents obtained that IT Telkom Purwokerto students agreed that they had trouble finding a room for the first time at IT Telkom Purwokerto. This recognition media is made using Augmented Reality with marker-based tracking technology; in the manufacturing process uses Unity and Vuforia a container for storing markers or markers. Development for this software uses the Agile model. Testing is the final stage before the application is presented to the user, using black-box and system usability testing. The test results on this application obtained results for black-box testing of 97.7% and System Usability Scale of 83.6, which can be concluded that users can use the application easily. Based on these results, it can be supposed that it is also included in the Excellent category with a B rating